2020
DOI: 10.1111/jdi.13249
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma irisin and glucose metabolism in pregnant women is modified by dietary n‐3 polyunsaturated fatty acid intake

Abstract: Aims/Introduction The role of irisin in maternal glucose metabolism and how it would respond to dietary n‐3 polyunsaturated fatty acid (n‐3 PUFA) intake remains unclear. This study aimed to explore whether maternal plasma irisin is associated with glucose metabolism and whether this association is modified by dietary n‐3 PUFA. Materials and Methods A total of 932 pregnant women (20–28 weeks’ gestation) aged 20–45 years were recruited. Dietary n‐3 PUFA was estimated using a validated quantitative food frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…This suggests that the increase in irisin during pregnancy is an adaptive response, to compensate for the increase in IR. Furthermore, maternal irisin showed a negative association with fasting plasma glucose (FPG) [90]. Several possible interpretations have been proposed to explain this finding.…”
Section: Irisin and Gestational Diabetes Mellitusmentioning
confidence: 96%
See 2 more Smart Citations
“…This suggests that the increase in irisin during pregnancy is an adaptive response, to compensate for the increase in IR. Furthermore, maternal irisin showed a negative association with fasting plasma glucose (FPG) [90]. Several possible interpretations have been proposed to explain this finding.…”
Section: Irisin and Gestational Diabetes Mellitusmentioning
confidence: 96%
“…However, it has been hard for studies to evaluate the association between irisin levels and maternal HOMA-IR, considering potential confounding variables such as age, BMI, physical activity, and nutritional status, which influence circulating irisin levels [23]. To reduce the potential influence of confounding factors, Cai et al used multiple linear regression analysis, and found an inverse association between maternal serum irisin levels and HOMA-IR [90]. This suggests that the increase in irisin during pregnancy is an adaptive response, to compensate for the increase in IR.…”
Section: Irisin and Gestational Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation